Predisposición de las hemorragias pos alumbramiento en relación con los componentes de riesgo obstétricos en gestantes por parto vaginal. Hospital Iquitos “César Garayar García” II-2 enero 2022- junio 2022 - Gozar Mena, Himmbler Alexei (2024)
Project Title: Predisposition of postpartum hemorrhages in relation to obstetric risk components in pregnant women undergoing vaginal delivery. Iquitos “César Garayar García” Hospital II-January 2, 2022- June 2022. General Objective: Determine the predisposition of post-birth hemorrhages in relation to the obstetric risk components in pregnant women undergoing vaginal delivery. Iquitos Hospital “César Garayar García” II-January 2, 2022 - June 2022. Methodology: The research will be in accordance with its basic purpose in view of the fact that it is oriented towards the exploration of new concepts without a specific and immediate practical purpose. Find out scientific principles and codes, creating a scientific concept. Therefore, it is called: basic scientific research. Research Design: This research will have a quantitative, descriptive epidemiological and correlational design approach. Population and Sample: The present study project, being epidemiological of post-birth hemorrhages in relation to the obstetric risk components in pregnant women due to vaginal delivery; We will work with the census population of postpartum patients who suffered bleeding after vaginal delivery, with a total of 193. The type of sampling will be non-probabilistic in an intentional modality, in which the inclusion and exclusion criteria will be taken into consideration. Data collection, processing and presentation technique: The study sample will be selected, whose information will be collected with the data collection form, which will be entered into the Excel office database. The medical records will be reviewed, identifying and recording the information on the items stipulated in the documentary analysis sheet. Biosafety measures will be used when collecting information. Information Processing: The Excel office database will be transferred to the SPSS 26 statistical software according to the variables and items of the collection instrument, for this the variables and labels of each variable will be coded in the database information. . Protection of Human Rights: Medical records will be reviewed to obtain data, maintaining strict confidentiality and under coding.